International Air Transportation Carriers: Evidence from SFA and DEA Technical Efficiency Results (1991-2000) - Michaelides, Panayotis G.; Belegri-Roboli, Athena; gKarlaftis, Matthew; Marinos, Theocharis (European Journal of Transport and Infrastructure Research, 2009)
In this paper we estimate technical efficiency in International Air Transport, by means of Stochastic Frontier Analysis (SFA) using a panel set of the world's twenty-four (24) largest network airlines, for the period 1991-2000. The results are compared to those from Data Envelopment Analysis (DEA), a popular approach for efficiency measurement in the literature. Findings suggest that airlines experience constant returns to scale, while technical efficiency ranges between 51% and 97% approximately. Furthermore, the level of technology experienced a slight increase, while the privatization of few of the airlines in the data set didn’t seem to affect their technical efficiency. Results from SFA and DEA do not vary significantly.